Assessment on the Application of Total Quality Management (TQM) in Improving Students’ Learning and Academic Performance in Government Secondary Schools in Manyoni District-Singida, Tanzania - Nange, Martina Mathew; Mkulu, Demetria Gerold (International Journal of Humanities and Education Development (IJHED), 2020)
This study aimed at assessing the implementation of TQM in government secondary schools in improving students' academic achievement in Manyoni district Singida region. The researcher used three objectives to guide the study. To examine the association among total quality management principles and students' school success in public secondary schools in Manyoni District, to identify the challenges encountered by school heads in the whole process of quality supervision in schools and learners' academic attainment and to identify possible measures to the challenges in the implementation of total quality management in public secondary schools in Manyoni District. The study employed total quality management theory that founded by Deming in 1950s. It employed a mixed approaches research design, specifically convergent parallel mixed-method research design. The study used probability and non[1]probability in selecting sample. A total of 164 respondents from four public secondary schools were involving in the current study. The major instruments used were questionnaires that had a coefficient coloration of 0.73 to prove the reliability of the instruments. Other instruments used were in-depth interview guide. The researchers employed Statistical Package for Social Sciences version 20 for analysis of quantitative data. The information were analysed using descriptive approaches such as frequencies, percentages, means, and standard deviations, and results presented using tables, pie charts, and bar graphs. Qualitative data were analysed by means of open coding, categories, meaningful themes, as well as summarization of data. The results indicated that total quality management ideologies were very crucial in enhancing academics development in secondary schools. However, the study found that total quality management in public secondary schools in Manyoni is not implemented effectively. Therefore the government should ensure that all secondary schools are implementing TQM